The Influence of Village Funds, Village Development Quality, and SDGs Achievement on Poverty in Sampang Regency - Mellysa Nur Awalia; Sutikno, Sutikno (Universitas Muhammadiyah Sorong, 2024)
The paradigm in solving poverty and development problems has always been a crucial discussion among researchers and academics. Poverty is synonymous with lack of income, lack of access to health, low education, and low infrastructure. This is considered a problem in hindering economic growth. This study aims to determine the influence of village funds, the quality of village development, and the achievement of SDGs (quality village education and prosperous healthy villages) on poverty. The research method used is a quantitative method and the type of data used is secondary data taken from the website of BPS Sampang Regency and the Ministry of PDT and Transmigration using cross section data in 2022. The collected data was analyzed using multiple linear regression with variables such as village funds, the building village index (IDM), village education quality, prosperous healthy villages, and poverty. The results of the study found that village funds, the building village index (IDM), and healthy prosperous villages had a significant effect on poverty in Sampang Regency. Meanwhile, quality village education does not have a significant effect on poverty in Sampang Regency.